Taking Stock An Update on Vietnam's Recent Economic Developments - Mishra, Deepak (Economic Updates and Modeling, 2010)
In the post-global economic crisis environment, Vietnam's economy continues to grow at a reasonably rapid and stable rate. While the speed of global economic recovery has been uneven across the world, Asia as a region has done particularly well. And within Asia, Vietnam's growth performance continues to be impressive. As shown in left panel of, Vietnam was one of the fastest growing economies in the East Asia and Pacific (EAP) region prior to the global economic crisis and has remained so in the post-crisis period as well1. After registering a real gross domestic product (GDP) growth of 5.3 percent in 2009, Vietnam's economy is expected to grow between 6.5-6.7 percent in 2010. Vietnam, like China, stands out not only for achieving a higher average growth rate but also a more stable growth path. This however has meant that the speed with which the Vietnam's economy is bouncing back from the lows of 2009 appears to be less impressive than countries that experienced negative growth last year. This edition of 'Taking Stock' a semi-annual publication from the World Bank attempts to understand the recent macroeconomic changes in Vietnam. It documents changes to the macroeconomic outcomes and policies with a view to inform policy discussions in the country. The analysis is mostly retrospective in nature, though discussions on prospective challenges and outlook are also briefly mentioned. Developments in the global economy in general and in the EAP region in particular are juxtaposed against Vietnam's own economic outcomes and policies to provide a more complete and nuanced picture of the issues